Glycerol hydrogenolysis into propanediols using in situ generated hydrogen – A critical review. Issue 1 (18th October 2012) - Martin, Andreas; Armbruster, Udo; Gandarias, Inaki; Arias, Pedro Luis
Abstract The rise in chemical transesterification of plant triglycerides towards biodiesel is unbowed and thus the available amount of glycerol is still increasing. The produced amount overruns the chemically used portion. Various ways to convert glycerol have been shown recently to yield attractive intermediates and final products. One of the options of future chemical utilisation of glycerol might be its conversion to propanediols (1, 2‐PDO (propylene glycol), 1, 3‐PDO (trimethylene glycol)) by hydrogenolysis. 1, 2‐PDO finds various applications in chemical industries; 1, 3‐PDO is mainly used for the manufacture of polymers. A synthesis route via glycerol might substitute present industrial syntheses using for example propylene oxide. Such an alternative synthesis route might run in the presence of externally fed hydrogen or by use of in situ generated hydrogen that can be supplied for example by glycerol aqueous phase reforming (APR) and/or catalytic transfer hydrogenation (CTH) using hydrogen donor molecules. A very attractive approach seems to be the use of formic acid as hydrogen donor for CTH because only carbon dioxide is liberated as a by‐product. This paper summarises most significant reports of the last decade, dealing with the production of PDOs via glycerol hydrogenolysis by in situ generated hydrogen.